2015
DOI: 10.1016/j.chemphys.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic calculations of the ground state energies and the critical distances for one-electron homonuclear quasi-molecules

Abstract: a b s t r a c tThe ground-state energies of one-electron homonuclear quasi-molecules for the nuclear charge number in the range Z ¼ 1 À 100 at the ''chemical'' distances R ¼ 2=Z (in a.u.) are calculated. The calculations are performed for both point-and extended-charge nucleus cases using the Dirac-Fock-Sturm approach with the basis functions constructed from the one-center Dirac-Sturm orbitals. The critical distances R cr , at which the ground-state level reaches the edge of the negative-energy Dirac continuu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 35 publications
3
24
0
Order By: Relevance
“…To conclude we have shown that the approach, based on the multipole expansions (12), (15) for solving the two-center DE, can be successfully applied for the compact nuclear quasi-molecules (d 100 fm), and allows to investigate the process of diving of discrete levels into the lower continuum in heavy ions collisions not only qualitatively (what could be performed within the monopole approximation), but also quantitatively. Calculated critical distances R cr for the levels 1σ g and 1σ u are in a good agreement with other computations [20,32,33,36,38,39,45]. Moreover, the results R cr for the 1σ u level significantly improve the most relevant values, which have been obtained early within the monopole approximation [39].…”
Section: σGsupporting
confidence: 86%
See 3 more Smart Citations
“…To conclude we have shown that the approach, based on the multipole expansions (12), (15) for solving the two-center DE, can be successfully applied for the compact nuclear quasi-molecules (d 100 fm), and allows to investigate the process of diving of discrete levels into the lower continuum in heavy ions collisions not only qualitatively (what could be performed within the monopole approximation), but also quantitatively. Calculated critical distances R cr for the levels 1σ g and 1σ u are in a good agreement with other computations [20,32,33,36,38,39,45]. Moreover, the results R cr for the 1σ u level significantly improve the most relevant values, which have been obtained early within the monopole approximation [39].…”
Section: σGsupporting
confidence: 86%
“…IV for the nuclear charge Z ∼ 87 − 100, as well as the results from the Refs. [32,33,45]. The difference between these results is caused by using various nuclear charge distributions and nuclear radii.…”
Section: Results For the Pure Coulomb Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the Bohr-Oppenheimer approximation, the one-electron problem is reduced to the Dirac equation with Coulomb potential of two nuclei at a fixed internuclear distance D. This problem was investigated previously by a number of authors, see, e.g., Refs. [15,20,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Majority of these works relied on the partial-wave expansion of the two-center potential in the center-of-mass coordinate system.…”
Section: Introductionmentioning
confidence: 99%